Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

If y=3x+5 and z=x^2+2x-5, what is yz?


Sagot :

Answer:  3x^3 + 11x^2 - 5x - 25

Work Shown:

yz = y(x^2+2x-5)

yz = y(x^2) + y(2x) + y(-5)

yz = x^2( y ) + 2x( y ) - 5( y )

yz = x^2( 3x+5 ) + 2x( 3x+5 ) - 5( 3x+5 )

yz = x^2*3x + x^2*5 + 2x*3x + 2x*5 - 5*3x - 5*5

yz = 3x^3 + 5x^2 + 6x^2 + 10x - 15x - 25

yz = 3x^3 + 11x^2 - 5x - 25